Evaluasi Status Mutu Air Sungai Samboja di Kecamatan Samboja Barat Kabupaten Kutai Kartanegara - Noor, Alfian; Abdunnur, Abdunnur; Kristiningrum, Rochadi; Aipassa, Marlon Ivanhoe; Ruslim, Yosep (Sekolah Tinggi Pertanian Kutai Timur, 2023)
Evaluation of the Water Quality Status of the Samboja River in Samboja District, Kutai Kartanegara Regency. The depletion of clean water due to pollution in rivers as part of the impact of decreasing water quality. Knowing the status of the water quality and quality of the Samboja River in Samboja District, Kutai Kartanegara Regency is the goal of this study. Data analysis to evaluate the status and water quality of the Samboja River is to take water quality samples at three points, namely downstream, middle, and upstream in two conditions of no rain and after rain. Then the water quality parameters are tested and compared with water quality standards using the Storet method and the pollution index method which refers to the Decree of the Minister of the Environment Number 115 of 2003 concerning Guidelines for Determining the Status of Water Quality. The results showed that the water quality status of the Samboja river spatially and temporally using the Storet method, class II water allocation was categorized as